SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN (SKMHT) UNTUK KREDIT DIATAS 1 MILYAR YANG DIPERPANJANG TERUS-MENERUS SELAMA MASA TENOR KREDIT - Ayang Fristia M (LPPM Universitas Bina Bangsa, 2023)
Giving credit to public is not only provided by banks but also be given by Non-Bank Financial Institutions (LPNB). The bank/LPNB will ask for collateral from debtor in order to get certainty that the debtor will pay off all of his obligations to the creditor and if the debtor defaults, the creditor can execute the guarantee. However, collateral binding is usually not directly tied to Deed of Granting Mortgage (APHT), but is bound first with A Power of Attorney to Charge for the Right (SKMHT). There are many factors which lead to the creation of A Power of Attorney to Charge for the Right (SKMHT), including unregistered land, the cost of increasing mortgage rights is relatively expensive, the credit tenor is short and the credit limit is small. Currently there are cases of lending with a maximum of IDR 1,000,000,000 (one billion rupiah) tied to SKMHT until the credit tenor ends